2012
DOI: 10.1111/j.1742-481x.2012.01006.x
|View full text |Cite
|
Sign up to set email alerts
|

Necrotising fasciitis in the central part of the body: diagnosis, management and review of the literature

Abstract: Necrotising fasciitis (NF) is characterised by rapidly spreading necrosis of the soft tissue and fascia. It is rare but can be fatal when not managed properly. The aim of this study is to evaluate the diagnosis, treatment and results such as mortality, morbidity and reconstructive options of NF localised in the central part of the body. The main goal is to emphasise upon the clinical symptoms for early diagnosis which is the most important factor in saving the lives of these patients. Between January 2000 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 27 publications
1
19
2
5
Order By: Relevance
“…As a corollary, it has become evident that a second-look procedure under general anesthesia was not always mandatory since most survivors underwent only one surgical debridement under anesthesia. It has been suggested that all patients should undergo a second look under general anesthesia and that these patients have a lower mortality rate, 3 but our data did not support this statement. While the repeated nature of debridements may be considered the accepted standard of care in these patients, this is not always predictive of outcome.…”
Section: Number Of Surgical Debridement Procedurescontrasting
confidence: 93%
See 1 more Smart Citation
“…As a corollary, it has become evident that a second-look procedure under general anesthesia was not always mandatory since most survivors underwent only one surgical debridement under anesthesia. It has been suggested that all patients should undergo a second look under general anesthesia and that these patients have a lower mortality rate, 3 but our data did not support this statement. While the repeated nature of debridements may be considered the accepted standard of care in these patients, this is not always predictive of outcome.…”
Section: Number Of Surgical Debridement Procedurescontrasting
confidence: 93%
“…1 However, considerable variability exists and authors have reported mortality rates ranging from 10% to 80%. [2][3][4][5][6][7][8][9] To our knowledge no prospective studies have been done on FG. Retrospective research has been directed to identifying both risk factors associated with the onset of FG and prognostic factors relating to patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…El diagnóstico precoz y la intervención quirúr-gica temprana son los dos factores más importantes que influyen en la sobrevida de los pacientes 4 Una herramienta útil para detectar tempranamente una FN es el LRINEC score (laboratory risk indicator for necrotizing fasciitis), una escala de puntuación diseñada a partir de los valores séricos de glucosa, creatinina, sodio, hemoglobina, glóbulos blancos y proteína C reactiva que nos sirve para distinguir las FN de otras infecciones de partes blandas. Los pacientes con puntuaciones mayores de 6 deben ser evaluados con especial cuidado, ya que se asocia a un valor predictivo positivo del 92% y un valor predictivo negativo del 96% para detectar FN.…”
Section: Introductionunclassified
“…Sin embargo, el LRINEC score no puede ser interpretado de manera aislada, ni tampoco servir para la toma de decisiones por sí solo. La exploración quirúrgica basada en un alto índice de sospecha continúa siendo el procedimiento de referencia (gold standard) para el diagnóstico 1,4 .…”
Section: Introductionunclassified
See 1 more Smart Citation